Relationship Between Leadership Styles and Affective Commitment among employees in National Anti-Drugs Agency (NADA) - Raemah Abdullah Hashim; Bushro Ahmad; Azhari Jamaluddin (2016)

(untitled)
The objective of this study is to investigate the relationship between different leadership styles, specifically Islamic, authentic and transformational leadership and affective commitment in National Anti-Drugs Agency (NADA). [ABSTRACT BY AUTHORS]